Answer:
x = 26
Step-by-step explanation:
The three angles form a straight line, so they will sum to 180
4x - 8 + 34 + 76- x = 180
Combine like terms
3x+ 102 = 180
Subtract 102 from each side
3x+102-102 = 180-102
3x= 78
Divide each side by 3
3x/3 = 78/3
x = 26
Answer:
x = 1
Step-by-step explanation:
![\frac{2}{3} x - \frac{5}{6} = - \frac{5}{12} x + \frac{1}{4} \\ \frac{2}{3}x + \frac{5}{12} x = \frac{1}{4} + \frac{5}{6} \\ \frac{8}{12} x + \frac{5}{12}x = \frac{3}{12} + \frac{10}{12} \\ \frac{13}{12} x = \frac{13}{12} \\ x = 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20x%20-%20%20%5Cfrac%7B5%7D%7B6%7D%20%20%3D%20%20-%20%20%5Cfrac%7B5%7D%7B12%7D%20x%20%2B%20%20%5Cfrac%7B1%7D%7B4%7D%20%20%5C%5C%20%20%5Cfrac%7B2%7D%7B3%7Dx%20%2B%20%20%5Cfrac%7B5%7D%7B12%7D%20%20x%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D%20%20%2B%20%20%5Cfrac%7B5%7D%7B6%7D%20%20%5C%5C%20%20%5Cfrac%7B8%7D%7B12%7D%20x%20%2B%20%20%5Cfrac%7B5%7D%7B12%7Dx%20%3D%20%20%5Cfrac%7B3%7D%7B12%7D%20%20%2B%20%20%5Cfrac%7B10%7D%7B12%7D%20%20%5C%5C%20%20%5Cfrac%7B13%7D%7B12%7D%20x%20%3D%20%20%5Cfrac%7B13%7D%7B12%7D%20%20%5C%5C%20x%20%3D%201)
W times 73 because product means multiply
Outcomes in a sample space :)
Answer:
Step-by-step explanation:
<u>The angles B and Q should be same, therefore:</u>
- Q = 4x + 2 and B = 15x - 64
<u>The equation below as per above, solving for x:</u>
- 4x + 2 = 15x - 64
- 15x - 4x = 64 +2
- 11x = 66
- x = 6
<u>Then the angle measures:</u>